Development of photovoltaics and possibility of it’s application in Kazakhstan - Musabek, G.K.; Taurbaev, T.I.; Mansurov, B.Z.; Kablanbekov, B.M.; Baiganatova, Sh.B.; Mukaev, S.B.; Lepesov, K.K. (Recent Contributions to Physics, 2012)
This review examines the global experience of the solar energy development for the period from 2009 to 2011. The review deals with the description of the relevance, the basic principles and concepts of the modern development of photovoltaic, the main technological solutions used in the world production of solar cells and modules, statistical analysis of the world photovoltaic market, as the description of development projects in the field of photovoltaics in the Republic of Kazakhstan.